PERANCANGAN FASILITAS KERJA AKTIVITAS PENGERINGAN TAHU PADA UKM TAHU AWI SAGUBA - Rambe, Erikson; Hasibuan, Rizki Prakasa (Computer Science and Industrial Engineering, 2022)
The role of humans as still has a big impact in every industrial action. Unlike machines that can be repaired by humans as workers, they still have limitations. Manual and repetitive work has a high risk of MSDs complaints due to manual work facilities. Tofu drying activities at the Tahu Awi Saguba UKM during tofu drying have the potential to pose a risk of MSDs because it is carried out manually, repeatedly with simple work facilities and non-ergonomic work postures. This study begins with the calculation of the NBM questionnaire. Research achievements show that there are complaints on the neck, shoulders, upper arms, back, waist, elbows, forearms, wrists and hands. The average achievement of the work risk score with REBA is 6 which is moderate and requires corrective action. In an effort to reduce this risk, a trolley rack design was carried out by implementing the EFD method. The achievements of the trolley rack design according to the ergonomic aspects, namely; ENASE. With the priority of designing a trolley rack to reduce pain in workers with weight (0.333) and a trolley rack specification target designed in harmony with worker anthropometry. Anthropometric data used during this design are TB, TSB, LB and GT.